Research Shows What Farmers Prefer In 30-Minute Farm Show - Bruce Johnson (Journal of Applied Communications, 1978)
This paper shows how two agencies, Cooperative Extension and Mississippi Educational Television Network, surveyed the prospective farm television audience in Mississippi and came up with a program format for "Farmweek."